XEN45 Gel Stent Combined with Healaflow Injectable Viscoelastic Implant - Eloy Villarreal; Eran Berkowitz; Beatrice Tiosano (Case Reports in Ophthalmological Medicine)
Purpose. To introduce a potential solution for failed glaucoma surgeries by proposing an optional surgical procedure in conjunction with the use of Healaflow (Anteis S.A., Geneva, Switzerland) as a spacer, which may potentially reduce the failure rate. Case Presentation. We present the outcomes of a surgical procedure involving the inferonasal implantation of an ab interno XEN gel stent (Allergan, Dublin, Ireland) in a 74-year-old male patient who was experiencing uncontrolled advanced glaucoma in his left eye. It is important to note that the patient had previously undergone several glaucoma surgeries and procedures in the same eye. During this particular procedure, we utilized Healaflow as a spacer by implanting the stent within a subconjunctival Healaflow “bubble.” At 6 months postoperatively, intraocular pressure remained on target. There was no need for additional topical medications, and no change in visual acuity was observed. Conclusion. For patients with a history of unsuccessful glaucoma surgeries and who are unsuitable candidates for tube shunt procedures or transscleral diode cyclophotocoagulation, an alternative option involves implanting the XEN45 stent in the inferior nasal region in conjunction with the use of subconjunctival Healaflow. This combined approach may provide a potential solution for managing glaucoma in these patients.